New Middle Cambrian bivalved arthropods from the Burgess Shale (British Columbia, Canada). (18th November 2013) - Legg, David A.; Caron, Jean‐Bernard; Lane, Phil
Abstract The morphology of two new bivalved arthropods, Loricicaris spinocaudatus gen. et sp. nov. and Nereocaris briggsi sp. nov. from the middle Cambrian (Series 3, Stage 5) Burgess Shale Formation (Collins Quarry locality on Mount Stephen, Yoho National Park, British Columbia, Canada), is described. The material was originally assigned to the genus Branchiocaris, but exhibits distinctive character combinations meriting its assignment to other taxa. Loricicaris spinocaudatus possesses an elongate and spinose abdomen comparable to the contemporaneous Perspicaris and Canadaspis, as well as chelate second head appendages and subtriangular exopods, comparable to Branchiocaris. Nereocaris briggsi possesses a laterally compressed carapace, elongate and delicate appendages and a medial eye located between a pair of lateral eyes on a rhomboidal eye stalk. Although undoubtedly congeneric with Nereocaris exilis from a slightly younger horizon of the Burgess Shale Formation, N. briggsi differs in overall proportions and segment number, warranting assignment to a new species. The newly described taxa were coded into an extensive cladistic analysis of 755 characters, and 312 extinct and extant panarthropods, including a variety of Cambrian bivalved arthropods from both the Burgess Shale and the Chengjiang Lagerstätten. Cambrian bivalved arthropods consistently resolved as a paraphyletic assemblage at the base of Arthropoda. Important innovations in arthropod history such as the specialization of the deutocerebral head appendages and a shift from a nekton‐benthic deposit feeding habit to a benthic scavenging/predatory habit, the symplesiomorphic feeding condition of Euarthropoda (crown‐group arthropods), were found to have occurred among basal bivalved arthropods.